Biomass Production Of Aureispira Sp. Ccb-qb1 And Its Application As A Novel Bioflocculant - Rahman, Nur Hasyimah Abdul (2022)
Bioflocculants are important to remove pollutants, especially organic particles and heavy metals from wastewater. Previous study showed that Aureispira sp. CCB-QB1 demonstrated cell aggregation when calcium ions are available. This suggested that these bacterial cells are capable to adsorb the waste materials and have a great chance to be a novel bioflocculant. Therefore, in this research, the methods for cultivation of Aureispira sp. CCB-QB1 inside a bioreactor was studied. Then, the biosorption activity of the dead cells toward heavy metals (Fe3+ and Cu2+) was tested. The QB1 dead cells were prepared by treating the living cells using 0.5 % of formaldehyde. The dead cells were discovered to show robust flocculating activity toward kaolin (initial concentration 0.2 %) in the presence of 7 mM CaCl2. For cultivation inside flasks, 5 ml of the dead cell suspension showed overall of 96 % of flocculating activity after shaken using both 150 and 200 rpm agitation speeds. Besides, both tryptone and peptone were found to highly supported the growth of QB1 cells. The presence of peptone in the cell culture also helps in the aggregation of the QB1 cells. For cultivation inside a bioreactor, QB1 culture conditions were optimized using Response Surface Methodology (RSM). The optimized conditions were 3.39 % of sea salt concentration, 0.9 % of peptone concentration, and 29 h of incubation period. Additionally